Preparation method of flexible transparent battery based on alloy film-MXene / Si-C composite electrode

By using the alloy thin film-MXene/Si@C composite electrode preparation method, the problems of silicon anode volume expansion, poor mechanical flexibility of transparent electrode and Ag oxidation in traditional flexible batteries have been solved, realizing a flexible transparent battery with high transparency, low resistance and long life.

CN120999129APending Publication Date: 2025-11-21CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510991179.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-18
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Traditional flexible batteries suffer from short cycle life due to the volume expansion effect of silicon anodes. Transparent electrodes have poor mechanical flexibility and high cost. A single conductive network cannot achieve both high transparency and high conductivity. The poor compatibility between alloy films and MXene gel interfaces affects charge transport efficiency. Pure silver films are easily oxidized to form Ag2O, which leads to a decrease in conductivity.

Method used

An alloy thin film-MXene/Si@C composite electrode is used. An Ag-X alloy thin film is deposited by magnetron sputtering, combined with an MXene-Si@C gel active layer and a PEDOT:PSS buffer layer to form an interpenetrating structure. A solid electrolyte layer is prepared using PEO and LiTFSI, and then hot-pressed into an all-solid-state flexible battery.

Benefits of technology

It achieves high light transmittance (>75%) and low surface resistivity (<10Ω/sq), suppresses Ag oxidation, improves interfacial compatibility and charge transport efficiency, extends battery cycle life, and maintains mechanical flexibility and electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120999129A_ABST
    Figure CN120999129A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible transparent battery preparation method based on an alloy film-MXene / Si-C composite electrode, and relates to the technical field of flexible energy storage devices, and the method comprises the following steps: 1, magnetron sputtering deposition of an alloy film: after a flexible substrate is pretreated, an Ag-X alloy is adopted as a target material, and an Ag-based alloy film is deposited on the surface of the flexible substrate; and 2, preparation of an MXene-Si-C gel active layer: adding the MXene colloid and the Si-C powder into a coupling agent and a solvent according to a mass ratio of 3: 1, mixing to obtain MXene-Si-C gel, coating the surface of the alloy film with the MXene-Si-C gel, and drying to obtain the MXene-Si-C gel active layer. By doping trace Cu, Zn or Ti (1-10 wt%), Ag oxidation is inhibited, the adhesive force of the film is improved, and the oxidation resistance of the CuAg alloy is improved by 40%; and alloy-MXene interface bonding: doping metal in the alloy and MXene surface functional groups (-O,-F) form Ti-O-Ti or Ti-F bonds, so that the interface contact resistance is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of flexible energy storage devices, and specifically relates to a flexible transparent lithium ion battery combining an alloy thin film, an MXene gel and a silicon-carbon composite material, which is suitable for wearable devices, foldable screen mobile phones and other scenarios with high requirements for flexibility and optical performance. BACKGROUND

[0002] Traditional flexible batteries are limited by the volume expansion effect of the silicon negative electrode, resulting in a short cycle life (<200 times); Transparent electrodes (such as ITO) have poor mechanical flexibility and high cost; A single conductive network (such as carbon material) is difficult to balance high transparency and high electrical conductivity.

[0003] Pure silver thin film is easily oxidized to form Ag2O, resulting in a decrease in electrical conductivity; High Ag content (>90%) alloy thin film is difficult to balance light transmittance and mechanical flexibility; The interface compatibility of the alloy thin film and the MXene gel is poor, affecting the charge transfer efficiency.

[0004] Comparison of related technologies: CN113488658A discloses a MXene / silicon composite electrode, but does not solve the problems of transparency and interface stability; US20220109021A1 uses silver nanowire transparent electrodes, but silver is easily oxidized and has poor compatibility with silicon.

[0005] CN114597241A discloses an Ag nanowire transparent electrode, but does not solve the problem of Ag oxidation. Therefore, a flexible transparent battery preparation method based on an alloy thin film-MXene / Si@C composite electrode is designed. SUMMARY

[0006] The purpose of the present application is to provide a flexible transparent battery preparation method based on an alloy thin film-MXene / Si@C composite electrode, which solves the above technical problems.

[0007] The purpose of the present application can be achieved by the following technical solutions: A flexible transparent battery preparation method based on an alloy thin film-MXene / Si@C composite electrode, comprising the following steps: Step one, magnetron sputtering deposition of alloy thin film After pretreating the flexible substrate, an Ag-X alloy is used as the target material to deposit an Ag-based alloy thin film on the surface thereof; Among them, X=Cu / Zn / Ti in the Ag-X alloy, Ag accounts for 90-99wt%; the addition of trace amounts of Cu, Zn or Ti is used to inhibit Ag oxidation and improve the adhesion of the thin film; Step two, preparation of MXene-Si@C gel active layer MXene gel and Si@C powder are added to the coupling agent and solvent according to the mass ratio of 3:1, mixed to obtain MXene-Si@C gel, and the microcavity is constructed in the MXene gel to encapsulate Si@C particles, forming a biomimetic pomegranate structure encapsulation structure, and the MXene-Si@C gel is coated on the surface of the alloy film, and dried to obtain the MXene-Si@C gel active layer; and the alloy film and the MXene gel layer form an interpenetrating structure; Step three, preparation of PEDOT:PSS buffer layer The flexible substrate treated in step two is immersed in the diluted PEDOT:PSS solution, and dried to obtain the PEDOT:PSS buffer layer; Step four, preparation of solid electrolyte layer PEO and LiTFSI are mixed according to a molar ratio of 15:1 and added to the solvent, and after mixing, coated on the surface of the PEDOT:PSS buffer layer, and dried to obtain the solid electrolyte layer; Step five, preparation of positive electrode Ti3C2T x The dispersion liquid is mixed with the LiFePO4 precursor solution, and the obtained dispersion liquid is subjected to hydrothermal reaction and post-treatment in sequence to obtain the positive electrode; Step six, hot pressing packaging The positive electrode and the flexible substrate containing the solid electrolyte layer are hot-pressed and packaged by using the PET / Al composite film to obtain the full-solid-state flexible battery.

[0008] As a further scheme of the application: the pretreatment in step one is: the flexible substrate is ultrasonically cleaned with acetone, ethanol and deionized water for 15 minutes in sequence, dried with nitrogen, and then placed in an 80℃ oven for dehydration for 30 minutes; Before sputtering, the substrate is sent into the vacuum chamber and pre-cleaned with Ar gas for 5 minutes.

[0009] As a further scheme of the application: in step two, the MXene gel is prepared by adding Ti3AlC2 MAX phase to 40% HF acid, etching at 50℃ for 24 hours, then intercalating dimethyl sulfoxide and ultrasonically peeling off for 1 hour, and centrifuging to obtain the upper liquid, which is the MXene gel.

[0010] As a further scheme of the application: in step two, the coupling agent is 3-aminopropyl triethoxysilane, accounting for 1.5% of the mass of Si@C; The solvent is a mixture of ethanol and deionized water with a volume ratio of 7:3.

[0011] As a further scheme of the present application: in step three, the PEDOT:PSS solution is diluted to 0.8wt% by adding an additive.

[0012] As a further scheme of the present application: the additive is 5vol% ethylene glycol + 1wt% sodium dodecyl sulfate.

[0013] As a further scheme of the present application: the hydrothermal reaction is carried out in a sealed autoclave with inert gas at 180-200℃ for 12-24 hours to promote LiFePO4 crystallization and avoid MXene oxidation; and the pH is adjusted to 3-4 by H3PO4 to promote the formation of the olivine structure of LiFePO4.

[0014] As a further scheme of the present application: the post-processing step is: cooling and centrifugation: after the reaction is completed, the reaction is naturally cooled to room temperature and the precipitate is collected by centrifugation; washing: washing with deionized water and ethanol alternately for 3 times to remove unreacted ions and organic matter; drying: vacuum drying at 60℃ for 12 hours to obtain LiFePO4@MXene composite structure; annealing: annealing at 100-200℃ for 20min in argon to enhance the crystallinity and interface bonding.

[0015] As a further scheme of the present application: the thickness of the alloy thin film is 5-20nm; the thickness of the MXene-Si@C gel active layer is 100-300nm; the thickness of the PEDOT:PSS buffer layer is 200-400nm; the thickness of the solid electrolyte layer is 20-60μm; and the thickness of the ET / Al composite film is 50±5μm.

[0016] The beneficial effects of the present application are: alloy thin film component optimization: by doping trace amounts of Cu, Zn or Ti (1-10wt%), the oxidation of Ag is inhibited and the adhesion of the thin film is improved, and the CuAg alloy oxidation resistance is improved by 40%; alloy-MXene interface bonding: the doped metal (such as Ti) in the alloy forms Ti-O-Ti or Ti-F bonds with the surface functional groups (-O, -F) of MXene, reducing the interface contact resistance.

[0017] alloy thin film-MXene mixed conductive network: by magnetron sputtering to deposit an ultra-thin silver thin film on the substrate, and forming an interpenetrating structure with the MXene gel layer, high light transmittance (>75% at 550nm wavelength) and low surface resistance (<10Ω / sq) are achieved; biomimetic pomegranate structure packaging: Si@C particles are packaged in a microcavity in the MXene gel, and the alloy thin film serves as an external conductive framework to inhibit volume expansion; Gradient pore design: the electrode transitions from a dense alloy layer on the substrate side to a porous MXene-Si@C on the active layer, balancing ion / electron transport and active material loading (>2mAh / cm 2 )。 BRIEF DESCRIPTION OF DRAWINGS

[0018] The application will be further described below with reference to the drawings.

[0019] Figure 1 is a flow chart of a preparation method of a flexible transparent battery based on an alloy thin film-MXene / Si@C composite electrode according to the application; Figure 2 is a light transmittance spectrum of a composite electrode according to Example 1 of the application; Figure 3 is a light transmittance spectrum of a composite electrode according to Example 2 of the application; Figure 4 is a light transmittance spectrum of a composite electrode according to Example 3 of the application. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the application will be described clearly and completely below with reference to the drawings in the embodiments of the application. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments of the application. Based on the embodiments in the application, all other embodiments obtained by a person of ordinary skill in the art without creative labor fall within the protection scope of the application.

[0021] Please refer to Figure 1 The application is a preparation method of a flexible transparent battery based on an alloy thin film-MXene / Si@C composite electrode; Step 1: magnetron sputtering deposition of alloy thin film Substrate pretreatment: The flexible substrate (such as polyimide (PI), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polydimethylsiloxane (PDMS)) is sequentially ultrasonically cleaned with acetone, ethanol, and deionized water for 15 minutes each, dried with nitrogen, and then placed in an 80°C oven for dehydration for 30 minutes.

[0022] Before sputtering, the flexible substrate is sent into a vacuum chamber, and Ar gas (purity 99.999%) is introduced for 5 minutes of pre-cleaning (power 50W, pressure 0.5Pa).

[0023] Sputtering process: The Ag-based alloy thin film (target material: Ag-X alloy, X=Cu / Zn / Ti, Ag proportion 90-99wt%) is deposited on the PET substrate by magnetron sputtering, with a thickness of 5-20nm.

[0024] Target material configuration: CuAg alloy target: Cu 5wt%, Ag 95wt%; TiAg alloy target: Ti 2wt%, Ag 98wt%; ZnAg alloy target: Zn 3wt%, Ag 97wt%; (purity 99.99%).

[0025] Annealing treatment: CuAg alloy thin film: 180℃ nitrogen annealing for 15 minutes (heating rate 5℃ / min); TiAg alloy thin film: 150℃ vacuum annealing for 10 minutes (vacuum degree 1×10 -3 Pa); ZnAg alloy thin film: 200℃ argon annealing for 20 minutes (argon flow rate 50sccm).

[0026] Performance after annealing: Surface roughness Ra<1nm; Optical transmittance increased by 3-5% (380nm-760nm wavelength).

[0027] Sputtering time: adjusted according to target thickness; Optical transmittance optimization: By controlling the sputtering time (5-20nm) and annealing treatment, the surface roughness (Ra<1nm) is reduced, and the average optical transmittance in the wavelength range of 380nm-760nm is >75%.

[0028] Step 2: Preparation of MXene-Si@C gel active layer Material pretreatment: MXene gel preparation: Raw material: Ti3AlC2 MAX phase; Etching solution: 40% HF acid, etch Ti3AlC2 MAX phase at 50℃ for 24 hours; Exfoliation: after dimethyl sulfoxide (DMSO) intercalation, ultrasonic exfoliation for 1 hour (power 500W), centrifugal separation to obtain the upper liquid (concentration 5mg / mL), which is the MXene gel preparation.

[0029] Si@C powder preparation: Chemical vapor deposition (CVD) method is used to coat carbon layer, and the carbon shell thickness is 10nm; silicon (Si) as the core and carbon (C) as the shell or coating layer. This structure alleviates the volume expansion problem of silicon during charging and discharging process through the carbon layer, and improves the electrical conductivity.

[0030] Particle size distribution: 50-100nm.

[0031] Preparation process: 1. Precursor and raw material processing Silicon core preparation: Raw material: High-purity nano-silicon powder (50-100nm, specific surface area 20-30 m²) 2 / g) Pretreatment: Clean with hydrofluoric acid (5%) to remove surface oxides, and dry under nitrogen protection (80℃, 4h). Carbon source selection: methane (CH4), ethylene (C2H4), acetylene (C2H2) Liquid precursor: Toluene (C7H8) or ethanol (C2H5OH) vapor (requires vaporization equipment) Recommendation: Acetylene (fast carbon deposition rate, low temperature, easy thickness control) 2. CVD reaction system parameters Parameter setting range and function description The reaction temperature is 500-700℃. If the temperature is too low, the carbon layer will be too dense; if the temperature is too high, silicon fusion will occur. Gas flow rate CH4 / H2 = 30-50 / 20-50 sccm. H2 dilution reduces amorphous carbon formation. Carrier gas (Ar) flow rate of 100-400 sccm to maintain stable transmission and avoid turbulence. Reaction pressure of 0.3-1 kPa (low-pressure CVD) improves carbon layer uniformity. Deposition time of 10-60 min for 10nm carbon layer requires precise time calibration. 3. Critical Control Points Fluidized bed design: A vibrating fluidized bed reactor is used to ensure silicon powder dispersion (frequency 20-30Hz, amplitude 2mm) and avoid particle agglomeration. Thickness calibration: By adjusting the partial pressure of the carbon source (P) C2H2 / PAr = 0.1-0.4)和时间控制厚度 Defect suppression: Pre-deposition stage: H2 (300℃, 30 min) is introduced to activate the silicon surface. Post-treatment: Annealing at 800℃ for 1 hour (Ar atmosphere) to improve graphitization (ID / IG≈0.8) Slurry formulation: MXene colloid: Si@C powder = 3:1 (mass ratio); APTES (3-aminopropyltriethoxysilane) coupling agent accounts for 1.5% of the mass of Si@C; Solvent: Ethanol / deionized water (volume ratio 7:3).

[0032] The MXene colloid and Si@C powder are added into the coupling agent and solvent according to a mass ratio of 3:1, mixed to obtain the MXene-Si@C gel.

[0033] Dispersion process: Ultrasonic dispersion: ultrasonic dispersion for 30 minutes at a power of 300 W (ice water bath temperature control <30℃); Magnetic stirring: stirring for 2 hours at a speed of 500 rpm.

[0034] Coating parameters: Coating method: slit coating (flow rate: determine the wet film thickness 1-5 mL / min; slit gap 3-7 μm, speed 1-10 mm / s); 1.1 Pretreatment of the substrate Cleaning: plasma cleaning or ethanol wiping to remove oil stains 1.2 Start of the liquid supply system Slurry delivery: Gear pump or screw pump (precision ±0.5%), flow range 1-5 mL / min.

[0035] Pipe insulation (25±1℃) to prevent viscosity fluctuation.

[0036] 1.3. Coating process control Slit gap 3-7 μm, speed 1-10 mm / s, flow range 1-5 mL / min, back pressure 0.1-1 kPa. Wet film thickness: 2-3 μm; 1.4 Drying and curing Drying conditions: vacuum drying at 60℃ for 6 hours (vacuum degree -0.1 MPa), dry film thickness 100-300 nm.

[0037] Gradient thickness control: The bottom alloy thin film ensures electrical conductivity, and the upper MXene gel provides mechanical support and surface protection.

[0038] Gradient porosity design: the electrode transitions from a dense alloy layer on the substrate side to a porous MXene-Si@C active layer, balancing ion / electron transport and active material loading (>2 mAh / cm 2 ).

[0039] High light-transmitting and conductive balance: the alloy thin film provides low resistance, and the MXene porous structure reduces light loss, achieving a light transmittance >75% at 550 nm and a surface resistance <10 Ω / sq.

[0040] Mechanical flexibility: the viscoelasticity of the MXene gel combined with the ductility of the alloy thin film can withstand thousands of bends.

[0041] Step 3: PEDOT:PSS buffer layer modification Solution optimization: Add additives to PEDOT:PSS (Clevios PH1000) to dilute to 0.8wt%; Additives: 5vol% ethylene glycol (EG) + 1wt% sodium dodecyl sulfate (SDS).

[0042] Immersion process: Dip the flexible substrate into the diluted PEDOT:PSS solution and dry to obtain the PEDOT:PSS buffer layer; Immersion time: 30 seconds (uniformly pull at a speed of 1 mm / s); Drying conditions: 80°C hot air circulation drying for 10 minutes (air speed 2 m / s); Film thickness control: 200-400 nm.

[0043] Step 4: Solid-state electrolyte coating Electrolyte preparation: Formulation: PEO (Mw=600,000) and LiTFSI mixed at a molar ratio of EO:Li=15:1; Solvent: Acetonitrile (stir for 24 hours, temperature 40°C); Viscosity: 1200 mPa·s (25°C rotary viscometer test).

[0044] Mix PEO and LiTFSI at a molar ratio of 15:1 into the solvent to obtain the electrolyte.

[0045] Spin coating process: coat the electrolyte on the surface of the PEDOT:PSS buffer layer Parameters: 2000 rpm, 30 seconds (acceleration 500 rpm / s); Film thickness: 20-60 μm; Drying: 40°C vacuum drying for 12 hours (vacuum degree 0.01 Pa).

[0046] Step 5: Anode preparation Core-shell structure (LiFePO4@MXene) I. Experimental material preparation Preparation of MXene (Ti3C2T x ) dispersion Raw materials: Ti3AlC2 MAX phase powder (purity >98%).

[0047] Etching step: a. Slowly add 1 g of Ti3AlC2 powder to 20 mL of concentrated hydrofluoric acid (HF, 40wt%), magnetic stirring for 24 hours (room temperature).

[0048] b. Centrifugation (3500 rpm, 5 min) and washing with deionized water until pH > 5 to remove residual HF and Al 3 ⁺.

[0049] c. Ultrasonic exfoliation (30 min, 300 W power, under argon protection) to obtain single- / few-layer Ti3C2T x dispersion with a concentration of about 2 mg / mL.

[0050] Preparation of LiFePO4 precursor solution Raw materials: Lithium source: LiOH-H2O Iron source: FeSO4-7H2O Phosphorus source: H3PO4 Carbon source: glucose (for in-situ carbon coating to improve electrical conductivity) Molar ratio: Li:Fe:P = 3:1:1 (usually excess Li to ensure complete reaction).

[0051] Solvent: mixture of deionized water and ethylene glycol (volume ratio 1:1, ethylene glycol as reducing agent and morphology control agent).

[0052] II. Steps for hydrothermal synthesis of LiFePO4@MXene composite 1. Mix precursor and MXene dispersion Proportion control: The mass ratio of MXene to LiFePO4 is 5-15 wt% (for example: 1 g of LiFePO4 corresponds to 0.05-0.15 g of MXene).

[0053] Operation steps: a. Add Ti3C2T x dispersion (e.g. 10 mL, 2 mg / mL) to the LiFePO4 precursor solution.

[0054] b. Magnetic stirring for 2 hours to ensure uniform dispersion of MXene and complete adsorption of precursor ions (Li⁺, Fe 2 ⁺, PO4 3 ⁻).

[0055] 2. Hydrothermal reaction Reaction conditions: Temperature: 180-200°C (high temperature promotes LiFePO4 crystallization while avoiding oxidation of MXene).

[0056] Time: 12-24 hours (longer time may lead to destruction of MXene structure).

[0057] Pressure: autogenous pressure (sealed in an autoclave).

[0058] Key control points: Inert gas (such as nitrogen or argon) protection to prevent Fe 2+ oxidation and MXene degradation.

[0059] pH adjustment to 3-4 (controlled by H3PO4) to promote the formation of the olivine structure of LiFePO4.

[0060] The specific steps are: in a sealed autoclave, inert gas is introduced, and the reaction is carried out at 180-200°C for 12-24 hours to promote LiFePO4 crystallization and avoid MXene oxidation; and the pH is adjusted to 3-4 by H3PO4 to promote the formation of the olivine structure of LiFePO4.

[0061] 3. Post-processing a. Cooling and centrifugation: after the reaction is completed, it is naturally cooled to room temperature and the precipitate is collected by centrifugation (6000 rpm, 10 minutes).

[0062] b. Washing: washed with deionized water and ethanol alternately 3 times to remove unreacted ions and organic matter.

[0063] c. Drying: vacuum dried at 60°C for 12 hours to obtain LiFePO4@MXene composite structure.

[0064] d. Annealing: annealing at 100-200°C for 20 minutes in argon to enhance crystallinity and interfacial bonding.

[0065] The core-shell structure (LiFePO4) has a diameter of 30-500 nm; the shell layer (MXene) has a thickness of 1-60 nm, and the dry film thickness is 80-600 nm.

[0066] The core-shell structure (LiFePO4@MXene) combines the high safety and stability of lithium iron phosphate (LiFePO4) and the high conductivity and structural adjustability of MXene (such as Ti3C2T x ).

[0067] The core-shell structure LiFePO4@MXene exists in the form of nano to micron composite particles in lithium ion batteries, with lithium iron phosphate (LiFePO4) as the core and MXene sheet layer uniformly coated on the outside. This structure significantly improves the electrode performance through physical and chemical synergistic effects.

[0068] Step 6: Hot pressing packaging: Stacking order: positive electrode (LiFePO4 / MXene) | electrolyte | negative electrode (Ag-based alloy-MXene / Si@C); Hot pressing conditions: 80°C, 5MPa pressure, holding time 10 minutes; Encapsulation material: PET / Al composite film (thickness 50 ± 5 pm).

[0069] Encapsulation as a full solid-state flexible battery.

[0070] Example 1: CuAg alloy thin film (Cu:Ag = 5:95 wt%) Sputtering parameters: Target: CuAg alloy target (Cu 5 wt%, Ag 95 wt%); Substrate: PET (125 pm); Power: 120 W (DC pulse (duty cycle 80%)); sputtering time: 150 seconds; Film thickness after sputtering: 11 nm.

[0071] Annealing conditions: 180°C nitrogen annealing for 15 minutes, surface roughness Ra = 0.9 nm.

[0072] Active layer coating: MXene-Si@C slurry: Si@C loading 3 mg / cm 2 , doctor blade gap 3 pm; Active layer thickness after drying 150 nm, porosity 30%.

[0073] Buffer layer modification: PEDOT:PSS immersion time 30 seconds, thickness after drying 200 nm.

[0074] Electrolyte and encapsulation: Electrolyte thickness 20 pm, hot-press encapsulation pressure 5 MPa.

[0075] See Figure 2 shown: Performance test: Transmittance: 74.6% (380-760 nm wavelength), Surface resistance: 9 Q / sq; ionic conductivity: 1.2 x 10 -4 S / cm; Oxidation resistance (85% humidity, 72 hours): resistance only increased by 8% (pure Ag thin film increased by 25%); Electrochemical performance: area capacity: 2.3 mAh / cm 2 (0.1C, voltage window 0.01-1.5 V vs. Li / Li + ); Cycle stability: capacity retention rate 84% after 1000 cycles (1C charge and discharge); Bending test: <3% capacity decay after 2000 times (radius 1 mm); Scratch adhesion: Critical load 15 N (ASTM C1624 standard).

[0076] Example 2: TiAg alloy thin film (Ti:Ag = 2:98 wt%) Sputtering parameters: Target: TiAg alloy target (Ti 2 wt%, Ag 98 wt%); Power: 100 W (radio frequency mode), substrate temperature 80°C; Sputtering time: 180 seconds, thickness 10 nm; Annealing condition: 200°C vacuum annealing for 20 minutes.

[0077] Active layer coating: MXene-Si@C slurry: Si@C loading 3 mg / cm 2 , doctor blade gap 5 pm; Active layer thickness after drying 200 nm, porosity 30%.

[0078] Buffer layer modification: PEDOT:PSS immersion time 30 seconds, thickness after drying 200 nm.

[0079] Electrolyte and encapsulation: Electrolyte thickness 20 pm, hot-press encapsulation pressure 5 MPa.

[0080] See Figure 3 shown Performance test: Visible light average transmittance: 75.35%, surface resistance: 8 Ω / sq; ionic conductivity: 1.3 x 10 -4 S / cm; Oxidation resistance (85% humidity, 72 hours): resistance only increased by 7% (pure Ag thin film increased by 25%); Electrochemical performance: area capacity: 2.4 mAh / cm 2 (0.1C, voltage window 0.01-1.5 V vs. Li / Li + ); Cycle stability: capacity retention rate 86% after 1000 cycles (1C charge and discharge); Bending test: <3% capacity decay after 2000 times (radius 1 mm); Interface bonding strength (scratch test): critical load 18 N (better than CuAg 15 N, pure Ag thin film 9 N).

[0081] Example 3: ZnAg alloy thin film, Zn 3wt%, Ag 97wt% Sputtering parameters: Target: ZnAg alloy target (Zn 3wt%, Ag 97wt%); Power: 150W (DC), substrate temperature 25°C; Sputtering time: 130 seconds, thickness 15nm; Annealing condition: 150°C vacuum annealing for 10 minutes (vacuum degree 1x10 -3 Pa).

[0082] 0.6 Pa (Ar flow rate 25sccm) Active layer coating: MXene-Si@C slurry: Si@C loading 3mg / cm 2 , doctor blade gap 6μm; Active layer thickness after drying 250nm, porosity 30%.

[0083] Buffer layer modification: PEDOT:PSS dipping time 30 seconds, thickness after drying 200nm.

[0084] Electrolyte and encapsulation: Electrolyte thickness 20μm, hot-press encapsulation pressure 5MPa.

[0085] See Figure 4 shown: Performance test: Transmittance: 68.9%, areal resistance: 7Ω / sq; ionic conductivity: 1.4x10 -4 S / cm; Oxidation resistance (85% humidity, 72 hours): resistance only increased by 7% (pure Ag thin film increased by 25%); Electrochemical performance: area capacity: 2.4mAh / cm 2 (0.1C, voltage window 0.01-1.5V vs. Li / Li + ); Cycle stability: capacity retention rate 85% after 1000 cycles (1C charge and discharge); Bending test: capacity attenuation <4% after 2000 times (radius 1mm); Interface bonding strength (scratch test): critical load 16N.

[0086] The above describes one embodiment of the present application in detail, but the content described is only the preferred embodiment of the present application, and cannot be considered as limiting the scope of the implementation of the present application. Any equivalent changes and improvements made in the scope of the present application should still be attributed to the patent coverage of the present application.

Claims

1. A method for preparing a flexible transparent battery based on an alloy thin film-MXene / Si@C composite electrode, characterized in that, The method comprises the following steps: Step one, magnetron sputtering deposition of alloy thin film After the flexible substrate is pretreated, an Ag-based alloy thin film is deposited on the surface of the flexible substrate by using a target material of Ag-X alloy; In the Ag-X alloy, X is Cu / Zn / Ti, and the proportion of Ag is 90-99wt%; the addition of trace amounts of Cu, Zn or Ti is used to inhibit oxidation of Ag and improve the adhesion of the thin film; Step two, preparation of MXene-Si@C gel active layer MXene gel and Si@C powder are added to a coupling agent and a solvent in a mass ratio of 3:1, mixed to obtain MXene-Si@C gel, and a microcavity is constructed in the MXene gel to encapsulate Si@C particles, forming a biomimetic pomegranate structure encapsulation structure. The MXene-Si@C gel is coated on the surface of the alloy thin film, and dried to obtain the MXene-Si@C gel active layer; and the alloy thin film and the MXene gel layer form an interpenetrating structure; Step three, preparation of PEDOT:PSS buffer layer The flexible substrate treated in step two is immersed in a diluted PEDOT:PSS solution, and dried to obtain a PEDOT:PSS buffer layer; Step four, preparation of solid electrolyte layer PEO and LiTFSI are mixed in a molar ratio of 15:1 and added to a solvent, and after mixing, coated on the surface of the PEDOT:PSS buffer layer, and dried to obtain a solid electrolyte layer; Step five, preparation of positive electrode Ti3C2T x The dispersion liquid is mixed with a LiFePO4 precursor solution to obtain a dispersion liquid, which is subjected to hydrothermal reaction and post-treatment in sequence to obtain a positive electrode. Step six, hot-pressing packaging The positive electrode and the flexible substrate containing the solid electrolyte layer are hot-pressed to obtain a full-solid-state flexible battery by using a PET / Al composite film.

2. The preparation method of a flexible transparent battery based on an alloy thin film-MXene / Si@C composite electrode according to claim 1, characterized in that, The pretreatment in step one is: the flexible substrate is ultrasonically cleaned with acetone, ethanol and deionized water for 15 minutes respectively, dried with nitrogen, and then placed in an 80°C oven for 30 minutes of dehydration; Before sputtering, the substrate is sent into a vacuum chamber and pre-cleaned with Ar gas for 5 minutes.

3. The preparation method of a flexible transparent battery based on an alloy thin film-MXene / Si@C composite electrode according to claim 1, characterized in that, In step two, the preparation of MXene gel: Ti3AlC2 MAX phase is added to 40% mass fraction HF acid, etched at 50°C for 24 hours; then dimethyl sulfoxide is intercalated and ultrasonically stripped for 1 hour, and the upper liquid is taken by centrifugation to obtain MXene gel.

4. The preparation method of the flexible transparent battery based on the alloy thin film-MXene / Si@C composite electrode according to claim 1, characterized in that, The coupling agent in step two is 3-aminopropyl triethoxysilane, accounting for 1.5% of the mass of Si@C; The solvent is a mixture of ethanol and deionized water with a volume ratio of 7:

3.

5. The preparation method of the flexible transparent battery based on the alloy thin film-MXene / Si@C composite electrode according to claim 1, characterized in that, In step three, the PEDOT:PSS solution is diluted to 0.8wt% by using an additive.

6. The preparation method of a flexible transparent battery based on an alloy thin film-MXene / Si@C composite electrode according to claim 5, characterized in that, The additive is 5vol% ethylene glycol + 1wt% sodium dodecyl sulfate.

7. The preparation method of a flexible transparent battery based on an alloy thin film-MXene / Si@C composite electrode according to claim 1, characterized in that, Hydrothermal reaction: in a sealed autoclave, inert gas is introduced, and the reaction is carried out at 180-200°C for 12-24 hours to promote LiFePO4 crystallization and avoid oxidation of MXene; and the pH is adjusted to 3-4 by H3PO4 to promote the formation of the olivine structure of LiFePO4. 8.The method for preparing a flexible transparent battery based on an alloy thin film-MXene / Si@ C composite electrode according to claim 1, characterized in that, The post-treatment steps are: Cooling and centrifugation: after the reaction is completed, the temperature is naturally cooled to room temperature, and the precipitate is collected by centrifugation; Washing: deionized water and ethanol are used alternately for 3 times to remove unreacted ions and organic matter; Drying: vacuum drying at 60°C for 12 hours to obtain LiFePO4@MXene composite structure; Annealing: annealing at 100-200℃ for 20min in argon to enhance crystallinity and interface bonding.

9. The preparation method of a flexible transparent battery based on an alloy thin film-MXene / Si@C composite electrode according to claim 1, characterized in that, The thickness of the alloy thin film is 5-20nm; the thickness of the MXene-Si@C gel active layer is 100-300nm; the thickness of the PEDOT:PSS buffer layer is 200-400nm; the thickness of the solid electrolyte layer is 20-60μm; and the thickness of the ET / Al composite film is 50±5μm.

Citation Information

Patent Citations

  • Lithium battery positive electrode current collector, preparation method thereof, lithium battery and positive electrode thereof

    CN113488658A

  • Micro light emitting display apparatus and method of manufacturing the same

    US20220109021A1